2016
DOI: 10.1177/1367006916644688
|View full text |Cite
|
Sign up to set email alerts
|

The time course of within and between-language interference in bilinguals

Abstract: Purpose: Recent research has provided support for linguistic coactivation, the view that the two languages of a bilingual are simultaneously active. Importantly, even if the system is fundamentally nonselective, the two languages of a bilingual can be activated to different degrees. The main contribution of the present paper is to empirically test what "different degrees of activation" really means. Differences could emerge in the timing or the magnitude of language activation. Methodology: Most of the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…This ended up being unfeasible for some labs within the timeframe available (which was more than a year), in some cases due to a high number of participants not meeting our strict criterion for inclusion as bilingual. This undoubtedly highlights the challenges for labs in recruiting bilingual infant samples, and moreover raises questions about how bilingualism should be defined, and whether it should be treated as a continuous vs. categorical variable (Anderson, Mak, Chahi, & Bialystok, 2018;Bialystok, Luk, Peets, & Yang, 2018;Incera & McLennan, 2018). Second, we had planned to explore the effect of different language pairs on IDS preference.…”
Section: Discussionmentioning
confidence: 99%
“…This ended up being unfeasible for some labs within the timeframe available (which was more than a year), in some cases due to a high number of participants not meeting our strict criterion for inclusion as bilingual. This undoubtedly highlights the challenges for labs in recruiting bilingual infant samples, and moreover raises questions about how bilingualism should be defined, and whether it should be treated as a continuous vs. categorical variable (Anderson, Mak, Chahi, & Bialystok, 2018;Bialystok, Luk, Peets, & Yang, 2018;Incera & McLennan, 2018). Second, we had planned to explore the effect of different language pairs on IDS preference.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similiar with the previos studies conducted by Brown et all. (2019), Incera & McLennan (2018), Fieder et all. (2019, Brooks & Kempe (2019) who consider that interference is one of factors which can affect negatively to the language acquisition in foreign language learning.…”
Section: Table 1 Types Amounts and Percentages Of Students' Errormentioning
confidence: 96%
“…Mouse-tracking measures have been implemented with bilingual populations ( Bartolotti and Marian, 2012 ; Incera and McLennan, 2016 , 2018a , b ). In 2016, my co-author and I reported the results of a Stroop task in which English-Spanish bilinguals, English-Other bilinguals (a group that included a wide range of language backgrounds), and English monolinguals responded to Spanish and English color words ( Incera and McLennan, 2016 ).…”
Section: Mouse Trackingmentioning
confidence: 99%
“…Temporal differences are often easy to visualize in figures, but relatively difficult to pinpoint with our current statistical methods. For example, in a mouse-tracking study in which a group of Spanish-English bilinguals participated in a Stroop task with Spanish and English color words ( Incera and McLennan, 2018b ), my co-author and I reported that within-language interference (English words with English response alternatives) emerged 80 ms earlier than between-language interference (Spanish words with English response alternatives). It is obvious that if we had used 100 ms time-windows we would have missed this 80 ms time difference.…”
Section: Suggestionsmentioning
confidence: 99%